Linking marketing and supply chain management in the strategy of demand chains via a review of literature reviews. Issue 9 (5th May 2021) - Bai, Bingfeng; Gao, Junjun; Lv, Yang
Abstract : Purpose: This paper aims to assess the links among these demand chain constructs by conducting a full-scale systematic review of all demand chain management (DCM) literature reviews published in marketing and operations management journals from 2013 to 2020. Marketing and supply chain management are central to DCM; thus, this study briefly describes the contributions to knowledge provided by the papers contained in this issue. In addition, some additional areas of research in which the DCM can be gainfully deployed are outlined. Design/methodology/approach: This paper makes a systematic literature review of 70 literature samples by means of content analysis and comprehensive analysis. These approaches guarantee a replicable, rigorous and transparent research process and minimize researcher bias. The analytical categories required for the content analysis are defined along the constructs of marketing and supply chain management. Findings: As can be expected, this paper highlights the key role of the two constructs in the strategy of DCM. In this light, the paper claims to provide evidence of a link between the constructs of marketing and supply chain management. This paper reviews the connotation of DCM through literature review, distinguishes the relationship between DCM and supply chain management from a strategic management perspective and discusses the future research direction. Research limitations/implications: This study assesses the link between the strategic constructs of marketing and supply chain management through research embedded in literature reviews, pinpointing research gaps and potential future research directions in the field. Contributing to DCM theory building, a thorough review provides qualitative comparison of the link between marketing and supply chain management. Originality/value: Although some literature reviews have been conducted in the past on the constructs of DCM, no full review of literature reviews aiming to test a strategic theoretical link in the demand chain related to supply chain and marketing.